2020
DOI: 10.1186/s12913-020-05619-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementing recommendations for inpatient healthcare provider encouragement of cardiac rehabilitation participation: development and evaluation of an online course

Abstract: Background: A policy statement recommending that healthcare providers (HCPs) encourage cardiac patients to enroll in cardiac rehabilitation (CR) was recently endorsed by 23 medical societies. This study describes the development and evaluation of a guideline implementation tool. Methods: A stepwise multiple-method study was conducted. Inpatient cardiac HCPs were recruited between September 2018-May 2019 from two academic hospitals in Toronto, Canada. First, HCPs were observed during discharge discussions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…30 In response to this, Canadian practitioners successfully delivered face-to-face and online in-service, education programs, to assist staff to use 'teaching moments.' 31 This study demonstrated that CE were pivotal in the provision of Phase-1-CR. However, CE were not employed by all hospitals, and not available after hours, on weekends and public holidays, thereby reducing their ability to see all eligible in-patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…30 In response to this, Canadian practitioners successfully delivered face-to-face and online in-service, education programs, to assist staff to use 'teaching moments.' 31 This study demonstrated that CE were pivotal in the provision of Phase-1-CR. However, CE were not employed by all hospitals, and not available after hours, on weekends and public holidays, thereby reducing their ability to see all eligible in-patients.…”
Section: Discussionmentioning
confidence: 78%
“…Further, whilst direct care staff identified lack of time for in‐patient education, another study identified ‘teachable moments’ in everyday health care, in which Phase‐1‐CR could be provided 30 . In response to this, Canadian practitioners successfully delivered face‐to‐face and online in‐service, education programs, to assist staff to use ‘teaching moments.’ 31 …”
Section: Discussionmentioning
confidence: 99%
“… % represented the percentage of papers that identified the subtheme as important; a. Ahmed et al., 2020; b. Birkin et al., 2016; c. Bonder et al., 2020; d. Devries et al., 2017; e. Hermes et al., 2019; f. Katzman et al., 2016; g. Keddem et al., 2020; h. Licskai et al., 2012; i. Melo & Bishop, 2020; j. Ross et al., 2018; k. Shrubsole, 2019; l. Svensson et al., 2017; m. Vogel et al., 2016; n. Wolfe et al., 2019; o. Hunter et al., 2020; p. Hunter, Kim, et al., 2020; q. Santiago et al., 2020; r. Srivastava et al., 2020; s. Wiecha et al., 2004; t. Williams et al., 2021; u. Newhouse & White, 2011; v. Puga et al., 2013; w. Ray et al., 2019; x. Walston et al., 2006 ( n = 24). …”
Section: Resultsmentioning
confidence: 99%
“…13 Correspondingly, following a needs assessment, a free, theoretically based 14 online course was developed for HCP as a tool to implement these findings (http://learnonthego.ca/Courses/promoting_patient_partici pation_in_CR_2020/promoting_patient_participation_in_ CR_2020EN/story_html5.html). 15 It educates HCP about CR, conveys the importance of their encouragement, as well as how they can provide strong, positive CR endorsement to patients at the bedside. No other courses addressing this are available internationally to our knowledge.…”
mentioning
confidence: 99%
“…Initial evaluation at a single center in Canada was positive. 15 A generic version has been created that is applicable globally to promote CR also in low-resource settings where it is greatly needed. It has been translated to four other languages.…”
mentioning
confidence: 99%